(untitled) (Research, Society and Development, 2023)
Crabs are abundant in the Pantanal and play a fundamental role in the trophic chain, as they are part of diet for mammals, birds, reptiles and amphibians in the Pantanal ecosystems. Approximately 0.63 individuals/m² of these organisms are found in the Pantanal, distributed in 6 species, including, Dilocarcinus pagei (Stimpson, 1861) and Trichodactylus petropolitanus (Göldi, 1886). This research investigated the richness, abundance, morphology and feeding habits of crabs in the Pantanal of Cáceres, under urban and remote área influence. Samplings were carried out at the Taiamã Ecological Station (168 km from Cáceres) and on the Paraguay River incorporated into the landscape of the Cáceres city - MT. The collections were made under banks of aquatic macrophytes using a 2 m long x 1 m wide nylon screen. In all, 256 crabs were collected, 226 belonging to the D. pageispecies and 20 to the T. petropolitanus species. The two species were found associated with the macrophytes Eichhornia crassipes and Eichhornia azurea, which form dense banks of plants that provide a place of refuge for crabs in terms of shelter, food and security against predators. The sampled organisms had preference in their food base for organic matter, stalk and root of macrophyte. Additionally, microplastic and other unidentified particulate matter were found in the food content, indicating damage to the diet and morphophysiology of the crabs. Our findings contribute to elucidate the diet of crabs in the Pantanal and project the effects of pollutants, such as microplastics, on these organisms and on the aquatic trophic chain, potentially affecting human health.